Distinct point defect behaviours in body-centered cubic medium-entropy alloy NbZrTi induced by severe lattice distortion. (1st May 2022) - Shi, Tan; Su, Zhengxiong; Li, Jing; Liu, Chenguang; Yang, Jinxue; He, Xinfu; Yun, Di; Peng, Qing; Lu, Chenyang
Graphical abstract: Abstract: The point defect properties of body-centered cubic medium-entropy alloy NbZrTi were studied by first-principles calculations. Due to severe lattice distortion, a significant portion of conventional vacancy and interstitial structures are unstable and require large structural relaxation, indicating an irregular energy landscape with large site-to-site variations. The average vacancy and interstitial formation energy are 0.95 eV ±  0.34 eV and 1.92 eV  ±  0.39 eV, respectively, much lower than that of Nb (2.77 eV and 4.38 eV). The vacancy migration energy exhibits a wide distribution extending to 0 eV, resulting in preferential vacancy migration through low barrier sites. The interstitial diffusion is slower than that of pure Nb due to the reduction of long <111> diffusion induced by the site-to-site variations in stable interstitial orientations. Ti atoms diffuse much faster than Nb and Zr atoms due to the preferential interstitial binding with Ti. The effect of atomic composition and short-range order on elemental and total interstitial diffusion was also investigated. The obtained first-principles results are important for the development of interatomic potentials for radiation damage studies. When irradiated with 3-MeV Fe ions at 675  ∘ C to a peak dose of ∼ 100 dpa, NbZrTi reduced the void formation at high temperature compared to Nb owing to its higher equilibrium vacancy concentration and closer mobility between vacancies and interstitial atoms.